Sarcoidosis with Arteriovenous Malformation in a 15-Year-Old Girl – The Rarest of the Rare - Qaiser, Iman; Nayani, Kanwal; Ahmed, Shakeel; Ali, Rehan; Atiq, Mehnaz (Frontiers in Pediatrics, 2015)
Introduction Sarcoidosis is an uncommon multi-system disorder with many possible complications. Arteriovenous malformations (AVMs) are a rare vascular complication of sarcoidosis. Case description A 15-year-old girl presented to the Pediatric Clinic at AKUH with pulmonary, hepatic, joint, and skin manifestations. Physical examination and investigations pointed toward sarcoidosis, including raised erythrocyte sedimentation rate, angiotensin converting enzyme (ACE), and alanine transaminase (ALT). An incidental finding of pulmonary arteriovenous malformation (PAVM) was noticed on echocardiography. She responded to oral corticosteroids, her ACE and ALT levels improved. There was lack of indication for pulmonary angio-embolization for her PAVM. On a 3-year follow-up, her condition improved and she is clinically well. Discussion Pulmonary arteriovenous malformation is an extremely rare complication of sarcoidosis, especially among the pediatric population. Hence, this is the first reported case of its kind. The relation between sarcoidosis and PAVM is difficult to establish; however, there are some theories. This condition may be treated depending on the symptoms. Since our patient did not have any significant symptoms of PAVM, she was treated for the underlying disease, i.e., sarcoidosis. Conclusion While dealing with patients having multi-system disorders like sarcoidosis, one must be very vigilant so as not to miss out on any complication. Regular follow-up visits should be scheduled to rule out new complications and to monitor the past ones.